The Cawthron Institute Culture Collection of Micro-algae: a significant national collection. Issue 2 (2nd April 2016) - Rhodes, L; Smith, KF; MacKenzie, L; Wood, SA; Ponikla, K; Harwood, DT; Packer, M; Munday, R
ABSTRACT: The Cawthron Institute Culture Collection of Micro-algae (CICCM) is a unique, nationally and internationally significant collection of 450 strains of approximately 100 micro-algae and 50 cyanobacteria species, both living and cryopreserved. The collection comprises 13 taxonomic classes and underpins research into the ecology and taxonomy of the isolates and the biotoxins they produce and their toxicity. The CICCM expanded significantly in the 1990s after a major harmful algae bloom event in the Hauraki Gulf, New Zealand. Since 2000, it has underpinned development of molecular detection tools and enabled development of new chemical testing methods for biotoxins in seafood. The tropical collection allows research into potential issues for New Zealand as the oceans warm, for example, the risks of ciguatera fish poisoning and palytoxins in seafood. Research results generated from isolates in the cyanobacterial collection have assisted national risk management regarding drinking water and informed the development of the New Zealand guidelines for managing cyanobacteria in recreational fresh waters. The actual living and cryopreserved micro-algae and cyanobacteria collection (without infrastructure) has a current estimated value of NZ$1.6 million.